Evaluation of the Adhesive Properties of Spores of Bacillus anthracis Vaccine Strains to the Mammalian Erythrocytes Using Photocolorimetry Technique - E. V. Pimenov; V. A. Oborin; A. G. Ivonin (Проблемы особо опасных инфекций, 2011)
Displayed are the results of studies concerning adhesion of spores of Bacillus anthracis vaccine strains to the erythrocytes of humans and other mammals using photocolorimetry technique. Determined are the differences in adhesive capacity of spores of B. anthracis vaccine strains № 55 VNIIVVM, STI-I and II Tsenkovsky. Discovered is the fact that the level of adhesive activity of B. anthracis № 55 VNIIVVM spores to the mammalian erythrocytes depends upon the sensitivity of the species to the anthrax agent.